(In)festar de vagalumes: a dança e a luta em Quando quebra queima - Alana dos Santos Schambakler (2024)
This work has as a parameter the context of the Uprisings developed by Georges Didi-Huberman and with this it makes an analysis of how the performative staging of Quando Quebra Queima by the collective occupation, incorporated the uprising of the secondary movement in the state of São Paulo, which occurred in 2015 and 2016, as a gesture of celebration and revolt. The abuse of State power linked to the precariousness and scrapping of state public education, which triggered the acts of protest, was problematized based on bell hooks' concept of education as a practice of freedom, articulating fundamental points of the research, with issues of race, gender and revolt. Paying attention to the experience of school occupations as an act of resistance and as a capacity for autonomy, we seek to associate it with Paulo Freire's perception of conscious human action as a presence in the world and in relation to each other in space. Regarding the aspect of performative action as an expanded field between art, education and life, we intertwine with Cassiano Sydow Qulici's reflections on performativity and work on oneself in the expanded scene, analyzing how dance and Funk were the languages chosen by the collective to recreate on stage the force of the event and the transformation of self in occupations.